the PELATIHAN PEMBUATAN BIOSORBEN DAUN KELAPA SEBAGAI ADSORBEN ION LOGAM BERAT DALAM RANGKA MENUMBUHKAN MINAT MENELITI SISWA DI SMAN 1 SINDUE : - - Dwi Juli Puspitasari; Husain Sosidi; MOHAMMAD MIRZAN; Prismawiryanti Prismawiryanti (Universitas Serang Raya, 2026)
Quality learning will produce quality graduates, namely those who meet 21st century skills, namely critical, creative, innovative thinking and analytical skills so that they can solve problems in everyday life. Students at SMAN 1 Sindue do not yet have an interest in conducting research. The purpose of community activity is to increase students' insight and attract students' interest in conducting research by utilizing materials from superior regional plants. The method used: socialization and demonstration to students of the Science Department, grades X and XI, SMAN 1 Sindue. Socialization begins by explaining the framework for conducting research, starting with finding the background of a study being conducted. Continued by providing material on literature reviews and research methods. The community service team demonstrated the Pb2+ ion absorption process assisted by students. Furthermore, an explanation was given on how to analyze the data obtained. Overall, this activity has opened students' insights in seeing problems in the environment so that they can be poured into a research proposal.